EFFECTIVENESS OF ROSELLA ON BONE REPAIR - Arief, Ridzky; Farida, Riska; Salsabila Wardhana, Safina; Pakpahan, Evie Lamtiur (Universitas prof. Dr. Moestopo (Beragama), 2025)
Background: Bone destruction can occur as a result of pathological processes that destroy bone components. The healing process from bone destruction can take time due to several factors such as the size and shape of the damage, metabolic factors, hormones, nutrition, and other factors. One of the plants that can repair bones is Rosella. Rosella flower (Hibiscus sabdariffa L) is a medicinal plant that grows in tropical and subtropical countries such as Saudi Arabia, India, Thailand, Malaysia, and Indonesia. Hibiscus sabdariffa L contains saponins, tannins, phenols, flavonoids, triterpenoids, and glycosides that can inhibit alveolar bone destruction. Purpose: To explain the effectiveness of Rosella (Hibiscuss Sabdariffa L.) on bone repair Methods: Journals were analyzed and accessed via Google Scholar, NCBI, and EBSCO from 2017 to 2024. Result: From 20 reference that have been found, after being analyzed based on inclusion and exclusion criteria, there is 20 reference has been choosed and 5 reference excluded. Conclusion: Rosella contain flavonoids that can promote the bone healing process, flavonoids can protect against bone loss by regulating signaling pathways that improve osteoblast function, by reducing the effects of oxidative stress or chronic low-level inflammation.